Exploring the Critical Challenges and Potent Effects of E-Learning - Eliyas, Sherin; Ranjana, P. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Corona Virus has affected the lives of all the people. The main purpose of this paper is to produce a survey which evaluates the increase of learning that has occurred in the usage of the online learning platforms. It even took several months for both the instructor and the students to finally adapt to the situation. Due to the pandemic, there has been a drastic change in the advancement of online learning platforms. Many students prefer learning on online platforms since it has been very convenient and very time consuming. Data Visualization provides an easy solution for this study. It helps in understanding and analysing the data given based on the results produced in the survey. This paper will help us understand the reasons for the increase and decrease of using online learning platforms and the various reasons behind each of them. We first split the entire concept into three different observations. Based on the research conducted in the first survey, the accuracy result from the first survey depicts that most of the students prefer using Great Learning since it provides the students with multiple free courses. In the second part of the research, almost the majority of the students have not completed (48.4%) the enrolled course. Few of the students have come at least halfway (14.5%) in the completion of the course. And the rest of the students (37.1%) responsibly completed the enrolled course. In the third part of the research, almost half the students who haven’t completed the course prefer that the main barrier faced among the students is the lack of interaction (36.7%).